2019
DOI: 10.18632/aging.102217
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sepsis among patients with COPD treated with fixed combinations of inhaled corticosteroids and long-acting Beta2 agonists

Abstract: This study aimed to compare the effect of budesonide/formoterol and fluticasone/salmeterol on the risk and outcomes of sepsis in COPD patients. We conducted this study using the Taiwan National Health Insurance Research Database. We included COPD patients prescribed with budesonide/formoterol or fluticasone/salmeterol between 2004 and 2011. Outcomes including sepsis and mortality were measured. 10,267 COPD patients who received fluticasone/salmeterol and 6,844 patients who received budesonide/formoterol were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Even in the subgroup analysis, the fluticasone/salmeterol group remained associated with a higher risk of active TB compared with the budesonide/ formoterol group. This intra-class difference has been shown in a previous study [21], and there may be different risks for other infectious diseases between budesonide/formoterol and fluticasone/salmeterol. In the PATHOS study, the rate of pneumonia and the pneumonia event rate per 100 patients were higher in fluticasone/salmeterol compared with budesonide/formoterol [19].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Even in the subgroup analysis, the fluticasone/salmeterol group remained associated with a higher risk of active TB compared with the budesonide/ formoterol group. This intra-class difference has been shown in a previous study [21], and there may be different risks for other infectious diseases between budesonide/formoterol and fluticasone/salmeterol. In the PATHOS study, the rate of pneumonia and the pneumonia event rate per 100 patients were higher in fluticasone/salmeterol compared with budesonide/formoterol [19].…”
Section: Discussionsupporting
confidence: 72%
“…In the PATHOS study, the rate of pneumonia and the pneumonia event rate per 100 patients were higher in fluticasone/salmeterol compared with budesonide/formoterol [ 19 ]. Another study showed that fluticasone/salmeterol carried a higher risk of sepsis (aHR, 1.15; 95%CI, 1.07–1.24) and septic shock (aHR, 1.14; 95%CI, 1.01–1.29) compared with budesonide/formoterol [ 21 ]. However, the present study is the first to confirm an intra-class difference for the risk of active TB between fluticasone/salmeterol and budesonide/formoterol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Not only can inhaled corticosteroids lead to increased rates of pneumonia; certain combinations have been associated with higher rates of sepsis, bacteremia, and skin infections among patients with COPD. [2][3][4] Questions that arise from this research include the following: Can we systematically enhance primary care providers' knowledge and experience with COPD management and align prescribing practice with more rigorous disease phenotypes while offering an algorithm of options for treatment for patients with dyspnea from other comorbidities? Can we build an educational program that is broadly generalizable to wide sectors of the population where pharmaceutical influence has traction and seeks to sell prescriptions?…”
mentioning
confidence: 99%